Effects of pre- and postnatal exposure to extremely low-frequency electric fields on mismatch negativity component of the auditory event-related potentials: Relation to oxidative stress. (2nd July 2016) - Akpınar, Deniz; Gok, Deniz Kantar; Hidisoglu, Enis; Aslan, Mutay; Ozen, Sukru; Agar, Aysel; Yargicoglu, Piraye
ABSTRACT: In our previous study, the developmental effects of extremely low-frequency electric fields (ELF-EF) on visual and somatosensory evoked potentials in adult rats were studied. There is no study so far examining the effects of 50 Hz electric field (EF) on mismatch negativity (MMN) recordings after exposure of rats during development. Therefore, our present study aimed to investigate MMN and oxidative brain damage in rats exposed to EF (12 kV/m, 1 h/day). Rats were divided into four groups, namely control (C), prenatal (Pr), postnatal (Po), and prenatal+postnatal (PP). Pregnant rats of Pr and PP groups were exposed to EF during pregnancy. Following birth, rats of PP and Po groups were exposed to EF for three months. After exposure to EF, MMN was recorded by electrodes positioned stereotaxically to the surface of the dura, and then brain tissues were removed for histological and biochemical analyses. The MMN amplitude was higher to deviant tones than to standard tones. It was decreased in all experimental groups compared with the C group. 4-Hydroxy-2-nonenal (4-HNE) levels were significantly increased in the Po group with respect to the C group, whereas they were significantly decreased in the PP group compared with Pr and Po groups. Protein carbonyl levels were significantly decreased in the PP group compared with C, Pr, and Po groups. EF decreased MMN amplitudes were possibly induced by lipid peroxidation.